Деякі практичні аспекти відповідальності співучасників за кримінальним правом США - Полянський, Євген Юрійович; Полянский, Евгений Юрьевич; Poljanskij, Е. (My University, 2012)
The author applies to specifi c features of Pinkerton doctrine – a concept of imputed liability for conspirators, arisen from judicial case. According to the concept, the conspirators are liable for all consequences caused by criminal activity regardless to personal guiltiness and personal contribution. Such approach engenders controversy in science, and in fact – needs revision.
Полянський Є. Ю. Деякі практичні аспекти відповідальності співучасників за кримінальним правом США / Є. Ю. Полянський // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 45. – С. 148-156.
Keywords: доктрина Пінкертона; відповідальність співучасників; відповідальність співучасників за незаплановану шкоду; ступінь участі у злочині; кримінальне право США; доктрина Пинкертона; ответственность соучастников; ответственность соучастников за незапланированный ущерб; степень участия в преступлении; уголовное право США; Pinkerton doctrine; responsibility partners; responsible partners for an unplanned damage; the degree of participation in the crime; US criminal law